Elsewhere - Koontz, Dean R. (Dean Ray), 1945- (Thomas & Mercer, 2020)
Since his wife left them, Jeffy Coltrane has worked to maintain a normal life for himself and his eleven-year-old daughter, Amity, but when a local eccentric entrusts Jeffy with hiding a strange device that allows people to jump between parallel planes, he and his daughter must outwit a man determined to obtain the device and use its grand potential for profound evil or the place that they call home may never be safe again.